A-Type Natriuretic Peptide Alters the Impact of Azithromycin on Planktonic Culture and on (Monospecies and Binary) Biofilms of Skin Bacteria Kytococcus schroeteri and Staphylococcus aureus - Ekaterina V. Diuvenji; Ekaterina D. Nevolina; Ilya D. Solovyev; Marina V. Sukhacheva; Sergey V. Mart’yanov; Aleksandra S. Novikova; Marina V. Zhurina; Vladimir K. Plakunov; Andrei V. Gannesen (Microorganisms, 2023)
It has been established that the human atrial natriuretic peptide is able to alter the effect of azithromycin on Kytococcus schroeteri H01 and Staphylococcus aureus 209P monospecies and binary biofilms. The effect of the hormone depends on the surface type and cultivation system, and it may have both enhancing and counteracting effects. The antagonistic effect of the hormone was observed mostly on hydrophobic surfaces, whereas the additive effect was observed on hydrophilic surfaces like glass. Also, the effect of the hormone depends on the antibiotic concentration and bacterial species. The combination of azithromycin and ANP led to an amplification of cell aggregation in biofilms, to the potential increase in matrix synthesis, and to a decrease in S. aureus in the binary community. Also, ANP, azithromycin, and their combinations caused the differential expression of genes of resistance to different antibiotics, like macrolides (mostly increasing expression in kytococci), fluoroquinolones, aminoglycosides, and others, in both bacteria.